(untitled) (American Journal of Islam and Society, 2003)
At its Third Regional Conference, the AMSS broke new ground, dispelling the popular image that Muslims are extremists and Islam is engaged in holy war against the West. Mayor Robert Cluck welcomed the participants, praised American Muslim organizations’ condemnation of 9/11, and thanked AMSS for informing Americans about Islam and the Muslim contribution to civilization through its publications and annual conventions. MSA president Laith Albataineh welcomed the participants on behalf of the students. In his introduction, Chairman Basheer Ahmed stated that extremism and terrorism were not unique to a single religion. He exhorted all peaceloving people to unite to rein in extremism before it gets out of control. Congressman Martin Frost (D-Texas), the guest of honor at the luncheon, referred to his post-9/11 statement encouraging every Texan to join him in resisting intolerance and bigotry. While condemning terrorism in the Middle East, he expressed his support for the "roadmap to peace" and a Palestinian state. Congressman Frost is known for his support of civil rights, getting more immigrants into the American armed forces, con stituent service, upholding the Bill of Rights, furthering his district’s eco nomic development, and assisting students’ career development. Moazam Syed, American Muslim Alliance president elect (Tarrant County) thanked the congressman; said that terror, hatred, and prejudice are alien to all religions; and that: "America will remain just and tolerant, even when confronted with terror and adversity." Bob Ray Sanders, Star Telegram staff writer and columnist, moderated the question and-answer session. Jamal Badawi (Saint Mary’s University, Halifax, Canada) dispelled the inaccurate notions that the Arabic words for "holy war’’ can be found in the Qur’ an, that kufr means "infidel," that Allah is the God of Muslims only, that Islam is exclusivistic, and that an unbeliever (kafir) does not have the same right to life as a Muslim, and several other often-misunderstood notions. He affirmed that practice or juristic opinions could not replace the Qur’an and ahadith, advocated an integrative contextual approach toward understanding these texts, and pointed out common pitfalls in their interpretation. His statements were well-received by both Muslims and non-Muslims. AMSS president Louay Safi analyzed the present extremism found in the Muslim world as being based on distorted interpretations of scripture ...